Assessment of Q-Heterochromatin in patiens with acute mountain sickness - Ibramov, A. I.; Brimkulov, N.N.; Mirrakhimov, M.M. (Acta Andina, 2025)
To determine genetic markers of the possible development of acute mountain sickness (AMS). we assessed the number and distribution of specific chromosomal regions, namely, Q-Heterochromatin regions (Q-HR) in 34 subjects who developed AMS after the ascent to 3600 m above sea level (Eastern Pamir). Controls were 36 subjects without signs of AMS. Q-HR analysis was performed using propil quinacrine mustard staining of the chromosomal preparations obtained from short-term lymphocyte culture. Unlike the controls, subjects with AMS were found to have certain differences in distribution of quantitative characteristics of chromosomal Q-HR variability; the total number of Q- HR in AMS subjects were 2.15 ± 0.19 in comparison to 1.06 ± 0.14 in the control group (P< 0,001). Thus, these data suggested the role of the hereditary predisposition in the development of acute mountain sickness.